CDK7 inhibition suppresses rheumatoid arthritis inflammation via blockage of NF‐κB activation and IL‐1β/IL‐6 secretion. Issue 2 (30th October 2017) - Hong, Honghai; Zeng, Yingmin; Jian, Wenxuan; Li, Lei; Lin, Liying; Mo, Yousheng; Liu, Meiling; Fang, Shuhuan; Xia, Yong
Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by joint swelling, joint tenderness and destruction of synovial joints, leading to severe disability. Anti‐inflammatory drugs and disease‐modifying anti‐rheumatic drugs (DMARDs) may improve RA process. However, in most patients the treatment effect is still not satisfactory. Cyclin‐dependent kinase 7 (CDK7) plays a well‐established role in the regulation of the eukaryotic cell division cycle, and recent studies indicated that it exerted anti‐inflammatory effect. In our previous research, we found that inhibition of CDK7 by highly selective inhibitor BS‐181 significantly impeded the development of collagen‐induced arthritis (CIA) mice. However, the underlying mechanism of CDK7 in RA remains to be explored. We elucidated the molecular mechanism of CDK7 inhibition in RA inflammation by administration of CDK7 highly selective inhibitor BS‐181 and siRNA‐CDK7. We found that both IL‐1β, IL‐6, IL‐8 and RANKL transcript levels and IL‐1β/IL‐6 secretion were effectively suppressed by BS‐181 treatment as well as CDK7 knockdown. Furthermore, CDK7 inhibition prevented NF‐κB signalling pathway activation and restrained p65 nuclear translocation. Moreover, CDK7 selective inhibitor BS‐181 also blocked phosphorylation of p65 in MH7A cells. These results strongly indicate that CDK7 inhibition by BS‐181 and siRNA‐CDK7 significantly suppresses rheumatoid arthritis inflammation, which may be via blockage of NF‐κB signalling pathway and IL‐1β/IL‐6 secretion.